The Socio-Economic Analysis of Strategic Planning on the Development of Public-Private Partnership: the Experience of Russian Regions - Ekaterina, Eremeeva; Natalya, Volkova; Tatiana, Khalilova; Aleksandr, Khalilov (International Journal of Criminology and Sociology, 2022)
The subject of the article is the item of what is the interrelation between such management frameworks as strategic planning and public-private partnership (PPP). Development of PPP seems relevant especially for particular regions of the country as such a concept allows the salvation of important socio-economic issues of territory and economizing budget resources at the same time. Aside from that, PPP might serve as a tool for stable region development. However, this requires carrying out a purposeful policy on developing public-private partnerships, which is going to be worked on and reflected in regional strategic plans. Within the framework of this deed based on specific Russian region experience, the research is taking place, how exactly perspectives of development and usage of PPP are reflected in strategy documents, and how this is being reflected on the development level of this economical concept. The basis of the study includes such methods as, compilation analysis of regional regulatory legal acts, score-based document-benchmarking study, and integral estimation of PPP development level in Russian Federation regions. The study results allowed estimation of Russian Federation regions experience, to highlight some issues obstructing PPP development, and to suppose a group of recommendations, and using them practically will allow for more accurate and complete securing perspectives of PPP development in regional strategic plans. Moreover, this in turn, will allow making PPP a more effective tool not for investments attraction only, but also for achieving stable development.